2020
DOI: 10.3389/fendo.2020.00573
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor in Breast Cancer: From Bench to Bedside

Abstract: Breast cancer (BC) is one of the most common malignancies and the leading cause of cancer-related mortality in women. Androgen receptor (AR) is frequently expressed in diverse BC subtypes. Accumulating evidence has revealed that AR might be a predictive or prognostic factor and a drug target in BC. AR expression and AR pathways differ in various BC subtypes, thereby resulting in controversial inferences on the predictive and prognostic value of AR. Herein, we summarized the roles of AR in different BC subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 109 publications
(130 reference statements)
2
35
1
3
Order By: Relevance
“…Accordingly, high AR mRNA levels observed in the datasets studied here give support to the insight that, in HER2+ tumors, the cooperation between AR and HER2 promotes ERK activation that regulates both HER2 and AR gene expression. As a consequence, there is a positive feedback loop [ 55 , 56 ] that may stimulate cell proliferation and the worse clinical outcomes usually observed in HER2+ BCs. AR mRNA expression in these cases is consistent with analyses performed using both BC molecular subtypes and IHC-surrogate subtypes, showing that AR mRNA levels are higher in HER2-enriched tumors compared to basal-like and TNBC tumors, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, high AR mRNA levels observed in the datasets studied here give support to the insight that, in HER2+ tumors, the cooperation between AR and HER2 promotes ERK activation that regulates both HER2 and AR gene expression. As a consequence, there is a positive feedback loop [ 55 , 56 ] that may stimulate cell proliferation and the worse clinical outcomes usually observed in HER2+ BCs. AR mRNA expression in these cases is consistent with analyses performed using both BC molecular subtypes and IHC-surrogate subtypes, showing that AR mRNA levels are higher in HER2-enriched tumors compared to basal-like and TNBC tumors, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Like the ER, AR is a member of the steroid-hormone receptor superfamily and can be expressed in high concentrations on breast cancer tissue [ 31 , 32 ]. Overall, 90% of MBC patients express AR-receptors on the surface of their tumour cells [ 29 , 33 ], which may serve as potential therapeutic targets [ 34 ], as is routinely observed in the treatment of prostatic adenocarcinoma [ 35 ]. ER-positive breast cancers are significantly more likely to be AR-positive than ER-negative tumours [ 36 ], with some studies suggesting AR status is a correlate of ER-alpha/PgR signaling [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the luminal AR (LAR) subtype, is associated with a transcriptomic profile enriched for AR expression signaling pathways and for having a luminal-like gene profile [ 89 , 143 , 150 , 151 ]. LAR tumors are characterized to be highly aggressive [ 152 , 153 ], which has emphasized the need for clarifying the role of AR in BC and promoted the development of several AR antagonists that are currently being tested in multiple clinical trials alone or in combination with other treatment strategies for ER− BC, which have been comprehensively reviewed by other authors [ 108 , 154 , 155 , 156 ]. To note, a phase II clinical trial comprising 424 TNBC patients, showed bicalutamide provide good results and have a considerable CBR at 6 months (19%) [ 157 ].…”
Section: Ar Signaling and Bcmentioning
confidence: 99%